Networking Aspects for Gaming Systems - Christos Bouras; Vassilis Poulopoulos; Vassilis Tsogkas; Ioannis Sengounis (Third International Conference on Internet and Web Applications (ICIW 2008), Athens, Greece, 2008)
As the evolution of computer technology introduces new advances in networks among others, online gaming becomes a new trend. Following the trends of our era, Games At Large IST Project introduces an innovative platform for running interactive, rich content multimedia applications over a Wireless Local Area Network. Games at Large project?s vision is to provide a new system architecture for Interactive Multimedia which will enhance existing CE devices such as, Set Top Boxes (STB), Small Screen and other devices, which are lacking both the CPU power and the graphical performance to provide a rich user experience. This paper presents the controllers? subsystem of the innovative mechanism that will be implemented in the context of Games at Large project. More specifically, it presents the general architecture of the complete system and focuses on the “capturing” and “execution of commands” modules at the different clients and the remote execution of the commands on server side. The client software captures the input from the different input devices, sends the commands over a Wireless Local Area Network and the server is responsible for receiving and executing the commands to the corresponding application.